2015
DOI: 10.1590/0037-8682-0178-2015
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcosis in Atlántico, Colombia: an approximation of the prevalence of this mycosis and the distribution of the etiological agent in the environment

Abstract: Introduction:Cryptococcosis is an invasive disease acquired by inhalation of infectious propagules from the environment. Currently, compulsory notifi cation of the spread of this disease is not required in Colombia. However, reporting of human immunodefi ciency virus (HIV)/acquired immune defi ciency syndrome cases to the National Surveillance System has suggested that there is a growing population at risk of contracting cryptococcosis. Few studies have described the occurrence of cryptococcosis in Colombia. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
(23 reference statements)
1
14
0
2
Order By: Relevance
“…A study regarding the prevalence of cryptococcosis in Atlántico, Colombia, showed that among the clinical isolates, C. gattii was responsible in 2.4% of them, while C. neoformans was in 90.4%; in the environment, only C. neoformans var. grubii was isolated in nine of the 2,068 total samples collected 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study regarding the prevalence of cryptococcosis in Atlántico, Colombia, showed that among the clinical isolates, C. gattii was responsible in 2.4% of them, while C. neoformans was in 90.4%; in the environment, only C. neoformans var. grubii was isolated in nine of the 2,068 total samples collected 16 .…”
Section: Discussionmentioning
confidence: 99%
“…After sub-Saharan Africa and followed by Southern Asia, Latin America stands in the third place with 54,400 yearly cryptococcal meningitis cases and 29,900 estimated deaths 16 . Isolation of clinical as well as environmental pathogenic species of Cryptococcus is not uncommon in Colombia 8-10,16 . In the national report (1997-2014), 1,535 of the isolates from patients with cryptococcosis (79% with AIDS) correspond to C. neoformans and 52 to C. gattii 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have characterized the properties of these yeasts that contribute to the colonization of new environmental niches (Granados and Castañeda, 2006;Randhawa et al, 2008;Ergin and Kaleli, 2010;Ergin et al, 2014;Sengul et al, 2019). With the exception of iatrogenic (Baddley et al, 2011) and zoonotic (Nosanchuk et al, 2000;Lagrou et al, 2005;Singh et al 2018) cases, Cryptococcus infection is caused by the inhalation of airborne basidiospores or desiccated yeast cells from the environment (Hull et al, 2005;Lin and Heitman, 2006;Velagapudi et al, 2009;Springer et al, 2013;May et al, 2016), emphasizing the importance of identifying the natural reservoirs of C. neoformans and the molecular links between environmental and clinical isolates and their association with disease (Litvintseva et al, 2005;Noguera et al, 2015;Chen et al, 2015;Kangogo et al, 2015;Spina-Tensini et al, 2017). In a recent study, MLST analysis revealed that some C. neoformans genotypes (especially ST63) in Mediterranean countries may be genetically linked (Cogliati et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…grubii was more prevalent (87.5%) than C. gattii (3.1%); VNI was the most prevalent (96.1%) molecular type, while VGII predominated in C. gattii isolates (54.3%) 4 . Previous data based on voluntary notifications indicated 41 cases of cryptococcosis reported between 1997 and 2014 in the Atlántico department of Colombia, with an annual average prevalence of 1.04 per 1 million inhabitants 5 .…”
mentioning
confidence: 99%
“…Each survey was submitted with a corresponding isolate/sample to the Universidad Metropolitana in Barranquilla for confirmation using conventional techniques. Species differentiation was performed by culturing samples/isolates in canavanine glycine bromothymol blue (CGB) agar 4,5 . Surveys and samples/isolates were finally submitted to the INS for confirmation and molecular typing.…”
mentioning
confidence: 99%